Sintesis de mecanismo watt i con pivotes fijos especificados para tres posiciones prescritas de las falanges de la mano de una persona usando el metodo de diadas estandar - Cruzado Cubas, Maicol Alex (2016)
This paper entitled "Synthesis of mechanism Watt I fixed pivots specified for three prescribed positions of the phalanges of the hand of a person using the method of standard dyads" was developed using the method of standard dyads with fixed pivots specified for mechanisms articulated four bar applied to this system of six bars. To determine the linkage of six rods type Watt I, it took the linkage of six bars as the composition of two articulated mechanisms of four separate bars together, making the fixed pivots O2 and O4 defined for the second link mechanism four bar and A1 and B1 as fixed pivots the first articulated four-bar mechanism all these points taken from the initial position prescribed one where the entire mechanism six bar is assembled as a whole, after that the movements made by each mechanism is analyzed separately thus obtaining the desired end cylindrical grip. By the method specified standard dyad with fixed pivots it was possible to synthesize a Watt I each link mechanism which meets the standard anthropometric established ranges. Representative lengths of each link referencing the proximal phalanges (44.95 mm), medium (29.92 mm) and distal (20.13 mm) of a prosthetic finger grip cylindrical. The circular path describes the mechanism for the cylindrical grip, and the desired positions of the distal phalanx defined with the rotation angles and for a rotation and of the proximal phalanx respectively. The result was simulated by the SolidWorks software.